Treatment of 'cripps pink' apples with nitric oxide in a controlled atmosphere ultra-low oxygen: Impacts on overall fruit quality and anaerobic compounds - Gularte P.S.* (2024)
© 2023 Elsevier B.V.The objective of this work was to evaluate the impact of nitric oxide application (in different doses 0, 1, 2, 5 e 10 μL L−1 of NO) on fruit quality and formation of anaerobic metabolism products of 'Cripps Pink' apples stored in a controlled atmosphere ultra-low oxygen (CA - ULO). Fruit were harvested at two maturity stages (less and more mature) and stored in CA - ULO (0.8 kPa of O2, <0.5 kPa of CO2, at temperature of 1.5 ± 0.2 °C, and 94 ± 2% RH) for four and eight months, followed by seven days of shelf life. Fruit in CA - ULO were treated weekly with 0, 1, 2, 5, or 10 μL L−1 of NO. In general, linear and quadratic models adjusted to quantitative levels of NO showed reduced respiration and ethylene evolution rates with the increase of NO concentrations. Also, the increase of NO concentration consistently reduced the activities of β-GAL and PG, preserved flesh firmness, and reduced the production of anaerobic metabolites (acetaldehyde and ethanol) and the incidence of decay in the fruit. These effects of NO concentrations on each quality attribute were dependent on maturity stage and storage duration (period in CA - ULO and/or subsequent shelf life). However, the results show that weekly application of 5–7 μL L−1 of NO during storage in CA - ULO maintained the quality of 'Cripps Pink' apples.